Motor speech disorders, dysphagia and aphasia in amyotrophic lateral sclerosis – diagnosis and management - Kluj-Kozłowska, Klaudia; Sitek, Emilia J. (Logopedia Silesiana, 2023)
In this paper we present the role of speech and language therapist in the interdisciplinary team focused on the management of patients with amyotrophic lateral sclerosis (ALS; Latin sclerosis lateralis amyotrophica, SLA). Depending on the clinical variant of ALS, speech disturbances may be the first disease manifestation or appear later in the disease course. In the differential diagnosis, it is useful to assess the type of dysarthria as well as describe the severity and profile of other deficits, such as dysphagia and aphasia. Assessment performed by a speech and language therapist is an ancillary examination in the differential diagnosis of clinical syndromes from frontotemporal lobar degeneration spectrum. Moreover, it enables devising optimal communication strategies and individualized therapeutic programme, not only applicable at a given disease stage but also aiming to support communication and prevent dysphagia.